Socialization and School Environment in an Inclusive Learning Community in the Province of Talca , Chile - María Teresa Muñoz Quezada; Boris Andrés Lucero Mondaca; Claudia Alejandra Cornejo Araya; Pablo Andrés Muñoz Molina; Nelson Eduardo Araya Saravia (Universidad Autónoma de Baja California, 2014)
Currently there is concern for promoting healthy and inclusive coexistence in schools. The aim of this research was to assess the perception of socialization and school environment in an inclusive school in the Province of Talca, Chile. We conducted a cross-sectional case study in a sample of 180 students, 193 parents and 21 teachers. A questionnaire evaluating school life was applied to students, parents and teachers and another assessing the school's social climate and bullying was applied to students in the last two grades. The results indicate that students perceive a positive social climate with a low risk of bullying. Issues of conflict were students' respect for the rules, being on friendly terms with the teachers, and disciplinary actions on the part of the families. We observed that the inclusive learning system contributes to school life and a positive climate and interactions.